Holistic approach to fraud management in health insurance - Furlan, Štefan; Bajec, Marko (Journal of Information and Organizational Sciences, 2008)
Fraud present an immense problem for health insurance companies and the only way to fight fraud is by using specialized fraud management systems. The current research community focussed great efforts on different fraud detection techniques while neglecting other also important activities of fraud management. We propose a holistic approach that focuses on all 6 activities of fraud management, namely, (1) deterrence, (2) prevention, (3) detection, (4) investigation, (5) sanction and redress, and (6) monitoring. The main contribution of the paper are 15 key characteristics of a fraud management system, which enable construction of a fraud management system that provides effective and efficient support to all fraud management activities. We base our research on literature review, interviews with experts from different fields, and a case study. The case study provides additional confirmation to expert opinions, as it puts our holistic framework into practice.